Exploiting the reactive oxygen species imbalance in high-risk paediatric acute lymphoblastic leukaemia through auranofin. - Karsa, Mawar; Kosciolek, Angelika; Bongers, Angelika; Mariana, Anna; Failes, Tim; Gifford, Andrew J; Kees, Ursula R; Cheung, Laurence; Kotecha, Rishi; Arndt, Greg M; Haber, Michelle; Norris, Murray D; et al. (2021)
BACKGROUND: The prognosis for high-risk childhood acute leukaemias remains dismal and established treatment protocols often cause long-term side effects in survivors. This study aims to identify more effective and safer therapeutics for these patients.